Luminescence turn-off detection of metal ions and explosives using graphene quantum dots - Jyotsna, Shubhra; Sadhu, Subha; Sharma, Vinay; Gupta, Preeti; Sharma, Geeta; Poddar, Pankaj (MRS Communications, 2022)
Green luminescent graphene quantum dots (GQDs) obtained from combustion of white printing paper were used for detection of fourteen different metal ions and six different explosives in an aqueous medium. These were obtained using a microwave-assisted synthesis process. After optimizing the experimental conditions (pH 6; quantum yield (QY) similar to 38.2%), a sensitive sensing system was developed to detect explosives and free residual metal ions in the environment based on fluorescence quenching of GQDs. The as-synthesized GQDs, as a sensing system, is most sensitive for Cu2+ ion and 2,4-DNP with a detection limit of 0.62 mu M and 0.50 mu M, respectively.